2020
DOI: 10.5658/wood.2020.48.5.618
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Anatomical and Physical-Mechanical Properties of the 8-Year-Old Superior Teakwood Planted in Muna Island, Indonesia

Abstract: Muna teakwood, especially from old stands, has been popular as raw material for timber industries in Indonesia for the past ten decades. Due to the scarcity of this wood, superior-grown seedlings of Muna teakwood have been developed and widely planted. Since there is no information on its characteristics, therefore, the aim of this research was to investigate wood characteristics of the 8-year-old superior-grown teak from Muna Island to ensure their proper utilization as raw material for wooden furniture. Wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…In general, the mean MCG under all treatments (Tables 3 and 4) were almost similar to a previous study of 30 to 31 years old teak from various clones in India (Shukla et al, 2011). However, the results were higher compared to the finding in 8-year-old clonal teak from Muna island (Savero et al, 2020). Moreover, it was reported that MCG from a fresh-cut tree would be around 33%-249% of the absolute wood-dried weight, which is strongly affected by differences in the part of the stem, site, age, harvested season, and tree dimension (Shmulsky and Jones, 2011).…”
Section: Green Moisture Content (Mcg)supporting
confidence: 86%
See 3 more Smart Citations
“…In general, the mean MCG under all treatments (Tables 3 and 4) were almost similar to a previous study of 30 to 31 years old teak from various clones in India (Shukla et al, 2011). However, the results were higher compared to the finding in 8-year-old clonal teak from Muna island (Savero et al, 2020). Moreover, it was reported that MCG from a fresh-cut tree would be around 33%-249% of the absolute wood-dried weight, which is strongly affected by differences in the part of the stem, site, age, harvested season, and tree dimension (Shmulsky and Jones, 2011).…”
Section: Green Moisture Content (Mcg)supporting
confidence: 86%
“…After a month, the mean wood moisture content of boards was achieved at 16.7 ± 0.4%, which was feasible to be used as specimen material for wood mechanical properties testing (Djati et al, 2015). Furthermore, the board were transformed into wood samples for mechanical properties testing, after reaching air-dried conditions (Djati et al, 2015;Savero et al, 2020). For the static bending test [modulus of elasticity (MOE) and modulus of rupture (MOR)], the sample dimension was 2 × 2 × 30 cm; and for the test of compression stress parallel (CSPL) and perpendicular to the grain (CSPD), a dimension of 2 × 2 × 6 cm was used.…”
Section: Wood Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, based on this, the quantitative data can be used to identify a wood and its geographical origin. The quantitative data can also be used to control the distribution of wood of endangered species in the wood market (de Palacios et al, 2020;Lee et al, 2020;Parades-Villanueva et al, 2018;Savero et al, 2020;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%